The effects of pre-induction intra venous dexmedetomidine on intraoperative sevoflurane requirement - Samantha Rampal, Hardyal Rampal (2008)
Dexmedetomidine is a highly selective a.2-adrenoreceptor agonist with potent sedative, anaesthetic-sparing and analgesic effects. Due to these effects, it has currently become an important adjuvant to current anaesthetic practi9es. The aim of this study is to evaluate if there is a reduction in the amount of expired fraction of intraoperative sevoflurane used with dexmedetomidine given as a single intravenous (i.v) dose of lJ.Lg/kg, 10 minutes before anaesthetic induction. A prospective, randomized double-blinded clinical trial was conducted on 60 patients planned for minor orthopaedic procedures less than 3 hours of duration. This was done in a time frame of twelve (12) months, between August 2006 and August 2007 at the operation theater of Hospital Universiti Sains Malaysia (HUSM). Sixty patients were randomized to receive either dexmedetomidine (n=30) or normal saline (n=30). Sedation score was evaluated using Ramsey sedation scale during and after drug administration, till patients were induced with fentanyl, sodium thiopentone and rocuronium. Anaesthesia continuation was maintained with 30%: 70% oxygen: nitrous oxide. Amount of sevoflurane administered was adjusted to maintain the bispectral index scale between 40 and 60. The expired fraction of sevoflurane, haemodynamic parameters and analgesia requirement were recorded at 5 minute intervals throughout the intraoperative period. The extubation time, which is the duration taken from the cessation of sevoflurane administration to the time patient is extubated was noted. The postoperative pain score (VAS) was documented at the recovery. Results show that there was a 27.8% reduction in the expired fraction of sevoflurane and a 25% drop ~ the thiopentone requirement in the dexmedetomidine group. The mean heart rate was also significantly lower in the dexmedetomidine compared to normal saline group [mean (CI): 69.20 (64.03, 74.37) versus 82.00 (72.12, 91.87) per minute, p = 0.005]. Patients, who received dexmedetomidine, were observed to be more sedated just before induction when compared to patients who received normal saline. The postoperative pain score (VAS) was significantly lower in the dexmedetomidine compared to normal saline group [mean (SD) 1.507 (0.275) versus 2.209(0.403), p= 0.005].There were no significant differences observed in the demographic characteristics, the mean systolic and diastolic blood pressure measurements and the extubation time between the two groups. In conclusio~ preoperative administration of a single dose intravenous dexmedetomidine decreased the expired fraction of sevoflurane by 27.8% in minor orthopaedic surgeries and has proven to be a good anaesthetic adjuvant as it not only blunts the haemodynamic response to intubation but also reduces the postoperative opioid requirement. Patients were noted to be. more comfortable, alert and complained of less pain during the postoperative period.